Time zones matter: The impact of distance and time zones on services trade - Elisabeth Christen (Johannes Kepler University of Linz, Department of Economics, 2012)
Using distance and time zone differences as a measure for coordination costs between service suppliers and consumers, we employ a Hausman- Taylor model for services trade by foreign affiliates. Given the need for proximity in the provision of services, factors like distance place a higher cost burden on the delivery of services in foreign markets. In addition, differences in time zones add significantly to the cost of doing business abroad. Decomposing the impact of distance into a longitudinal and latitudinal component and accounting for differences in time zones, it is possible to identify in detail the factors driving the impact of increasing coordination costs on the delivery of services through foreign affiliates. Working with a bilateral U.S. data set on foreign affiliate sales in services this paper examines the impact of time zone differences and East-West and North- South distance on U.S. outward affiliate sales. Both distance as well as time zone differences have a significant positive effect on foreign affiliate sales. By decomposing the effect of distance our results show that increasing East-West or North-South distance by 100 kilometers raises affiliates sales by 2%. Finally, focusing on time zone differences our findings suggest that affiliate sales increase the more time zones we have to overcome.
Keywords: F14; F21; F23; L80; 330; Foreign Affiliates Trade; International Trade in Services; Coordination Costs; Time zones; Entfernung; Zeit; Transaktionskosten; Ausländische Tochtergesellschaft; Schätzung; USA